The Role of Notaries in the Transaction Process and its Implications for the Validity of Land Documents under the Law - Simanjuntak, Kevin Malinowski; Tiaranda, Muhammad Fachreza; Samosir, Tetti (JURNAL AKTA, 2025)
This study discusses the role of notaries in the land transaction process in Indonesia and its legal implications for the validity of land documents. Notaries as public officials have the authority to make authentic deeds that serve as the legal basis for the transfer of land rights. The involvement of notaries in every stage of the transaction, from verifying the identities of the parties to making and ratifying the deed, plays an important role in creating legal certainty and preventing disputes in the future. However, in practice, challenges are still found such as abuse of authority by unscrupulous notaries and low public awareness of the importance of the legality of land transactions. This study uses a normative legal method with a qualitative approach, examining relevant laws and regulations and legal literature. The results of the study indicate that although the role of notaries has made a significant contribution to the validity of land documents, supervision and guidance of the notary profession need to be improved, and legal education for the community needs to be expanded in order to create a more transparent, accountable, and legally secure land system.